Perencanaan Pembangkit Listrik Tenaga Surya Hybrid Pada Area Parkir Gedung Dinas Cipta Karya, Dinas Bina Marga Dan Pengairan Kabupaten Badung - Abit Duka, Eric Timotius; Setiawan, I Nyoman; Ibi Weking, Antonius (Jurnal SPEKTRUM; Vol 5 No 2 (2018): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2018.v05.i02.p09, 2018)
The increasing demand for electrical energy in Bali requires additional electrical energy supply, while conventional energy such as petroleum, coal and natural gas continue to be used. Therefore, the utilization of non-conventional energy like solar energy should be increased. One of provision of non-conventional electric energy which is ready to be widely used is using PLTS Photovoltaic technology. The data analysis in this study uses manual calculation method to calculate electric power requirement, setting the result for electrical power, calculating the amount and capacity for solar module and inverter, calculating slope angle and location of solar module. PLTS uses a hybrid system with PLN, which works automatically to be controlled by the inverter control system. PLTS capacity of 148,274 kW supply 30% of the electrical energy consumption in the building of 2,310 MWh.